Exogenous Sphingosine-1-Phosphate Boosts Acclimatization in Rats Exposed to Acute Hypobaric Hypoxia: Assessment of Haematological and Metabolic Effects - Chawla, Sonam (Public Library of Science, 2014)
BACKGROUND: The physiological challenges posed by hypobaric hypoxia warrant exploration of pharmacological entities to improve acclimatization to hypoxia. The present study investigates the preclinical efficacy of sphingosine-1-phosphate (S1P) to improve acclimatization to simulated hypobaric hypoxia. EXPERIMENTAL APPROACH: Efficacy of intravenously administered S1P in improving haematological and metabolic acclimatization was evaluated in rats exposed to simulated acute hypobaric hypoxia (7620m for 6 hours) following S1P pre-treatment for three days. MAJOR FINDINGS: Altitude exposure of the control rats caused systemic hypoxia, hypocapnia (plausible sign of hyperventilation) and respiratory alkalosis due to suboptimal renal compensation indicated by an overt alkaline pH of the mixed venous blood. This was associated with pronounced energy deficit in the hepatic tissue along with systemic oxidative stress and inflammation. S1P pre-treatment improved blood oxygen-carrying-capacity by increasing haemoglobin, haematocrit, and RBC count, probably as an outcome of hypoxia inducible factor-1α mediated erythropoiesis and renal S1P receptor 1 mediated haemoconcentation. The improved partial pressure of oxygen in the blood could further restore aerobic respiration and increase ATP content in the hepatic tissue of S1P treated animals. S1P could also protect the animals from hypoxia mediated oxidative stress and inflammation. CONCLUSION: The study findings highlight S1P’s merits as a preconditioning agent for improving acclimatization to acute hypobaric hypoxia exposure. The results may have long term clinical application for improving physiological acclimatization of subjects venturing into high altitude for occupational or recreational purposes.